An international training program in library and information science : looking backward and forward / Paul Nieuwenhuysen - Nieuwenhuysen, Paul (2011)
The aim of this study is to improve the subsequent editions of an international training program in information management. Up to now 15 editions have been organized, coordinated by the author of this paper. About half of the participants work in developing countries in Asia. Each program takes place mainly in Brussels, Belgium, for about three months. One program has been organized each year, on average. The following are research questions: How to obtain financial support? How to organize the management of the program? How to exploit the fast evolution of ICT, to announce each new program? Same question for the communication with participants before and during the program. How to improve the use of computers and Internet by the participants? How to cope with the heterogeneity of the participants? Which contents to provide in the curriculum? Which types of learning experiences should we offer in this kind of training program? How to adapt to the specific needs of the students? How to assist the participants in translating their experience into a support for their future work? How to motivate the participants to use the training for concrete implementations in their home institute? How to deal with the reality that there is not just one solution for each challenge, while participants want to receive concrete solutions for needs in their home organization? What can be the function of assessment of each participant in such programs? How to provide a basis for future professional contacts among participants? How to use the program not only for professional development, but also as eye opener to other cultures? How to follow-up progress made by participants in their home organization? The training programs have served as lively laboratories to investigate how we can improve them. For each of the research questions above, we describe the situation during the first programs, the changes that we made during subsequent programs, and our view on the success of the various attempts towards improvement